2020
DOI: 10.1093/ofid/ofaa263
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Hepatitis C Virus Treatment in the New York City Jail Population: Successes and Challenges Facing Scale up of Care

Abstract: Background The population detained in the New York City (NYC) jail system bears a high burden of hepatitis C virus (HCV) infection. Challenges to scaling up treatment include short and unpredictable lengths of stay. We report on the clinical outcomes of direct-acting antiviral (DAA) treatment delivered by NYC Health + Hospitals / Correctional Health Services (CHS) in NYC jails from 2014-2017. Methods We performed a retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…(63) There have also been increased models of patients being treated on site in correctional facilities. (64,65) Telemedicine has emerged as an promising model of HCV treatment in prisons, obviating challenges associated with transporting prisoners to off-site clinics. (66) Efficacy of telemedicine in HCV treatment was demonstrated beginning during the pre-DAA era through Project ECHO (Extension for Community Healthcare Outcomes; discussed subsequently) and when the Virginia Department of Corrections partnered with an academic medical center to treat 59 inmates.…”
Section: Correctional Populationsmentioning
confidence: 99%
“…(63) There have also been increased models of patients being treated on site in correctional facilities. (64,65) Telemedicine has emerged as an promising model of HCV treatment in prisons, obviating challenges associated with transporting prisoners to off-site clinics. (66) Efficacy of telemedicine in HCV treatment was demonstrated beginning during the pre-DAA era through Project ECHO (Extension for Community Healthcare Outcomes; discussed subsequently) and when the Virginia Department of Corrections partnered with an academic medical center to treat 59 inmates.…”
Section: Correctional Populationsmentioning
confidence: 99%
“…Nineteen studies were identified assessing recurrence in high‐risk patients who achieved SVR following DAAs therapy 14,15,21,27‐29,45‐57 . The median follow‐up time post‐SVR was 17 months (interquartile range, 9‐21).…”
Section: Resultsmentioning
confidence: 99%
“…14,15,21,[27][28][29][45][46][47][48][49][50][51][52][53][54][55][56][57] The median follow-up time post-SVR was 17 months (interquartile range, 9-21). Of those studies, four evaluated the risk in prisoners, 15,49,53,56 S2).…”
Section: High-risk Hcv-mono-infected Populationmentioning
confidence: 99%
“…Although prisons have rolled out more comprehensive HCV treatment programs, coordination of HCV treatment in jails is problematic as detained people often have short or uncertain periods of detainment. There is increasing evidence that people who are in jail can be successfully treated with HCV medications, even when they are discharged mid–treatment course [ 24 ].…”
Section: Discussionmentioning
confidence: 99%